1995
DOI: 10.1039/ft9959101557
|View full text |Cite
|
Sign up to set email alerts
|

FTIR studies of adsorption of NO, NO2 and N2O on layered V2O5/ZrO2

Abstract: The adsorption of NO, NO, and N 2 0 at various temperatures on mono-and multi-layered V20,/Zr0, catalysts prepared by t h e gas-phase method h a s been investigated by IR spectroscopy. On t h e reduced samples of both mono-and multi-layer catalysts, NO is adsorbed giving mono-and di-nitrosylic species. On t h e oxidized form of t h e monolayer catalyst, only nitrite and nitrate species are formed and no nitrosylic species are formed. NO2 adsorbed on reduced multilayer catalysts exhibits IR bands due to nitrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 14 publications
2
23
1
Order By: Relevance
“…Miyata et al 31 , which they assigned to bridged, bidentate, and monodentate species, respectively. These authors 30 believe that the respective nitrato species form after interaction of NO 2 with oxygen from the vanadyl groups. By analogy to these results, we can assign the bands at 1639 and 1573 cm -1 in our spectra to the ν as -(NO 2 ) stretching modes of bridged and bidentate NO 3 -complexes.…”
Section: Redox Properties Of Vanadium Ions In V X O Y /Sba-15mentioning
confidence: 99%
See 1 more Smart Citation
“…Miyata et al 31 , which they assigned to bridged, bidentate, and monodentate species, respectively. These authors 30 believe that the respective nitrato species form after interaction of NO 2 with oxygen from the vanadyl groups. By analogy to these results, we can assign the bands at 1639 and 1573 cm -1 in our spectra to the ν as -(NO 2 ) stretching modes of bridged and bidentate NO 3 -complexes.…”
Section: Redox Properties Of Vanadium Ions In V X O Y /Sba-15mentioning
confidence: 99%
“…18 Summarizing, these results show that CO is a good probe molecule for determination of the oxidation state, but not the coordination state of surface vanadium ions. Previous studies on NO adsorption on supported vanadia have shown that both V 4+ and V 3+ ions can form dinitrosyls, 17,[29][30][31][32] and it was concluded that NO is a better probe molecule for determining the coordination state of vanadium sites. 29 For a detailed understanding of catalyst properties, the use of materials with well-defined structure is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors [10][11][12] have reported that nitrosylic species cannot form on pure zirconia, whereas others [13][14][15] have observed coordination of NO to Zr 4+ sites. Mononitrosyl species have been found on sulfated zirconia.…”
Section: Introductionmentioning
confidence: 99%
“…However, interpretations of the bands in this region are quite contradictory. A typical example is the band at 1180-1190 cm -1 , which has been assigned to nitrite 10,13,15 or nitrate 12 species. Greater amounts of NO x species (mainly nitrates and nitrites) on ZrO 2 are observed when NO and O 2 are coadsorbed at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation